2005
DOI: 10.1159/000087164
|View full text |Cite
|
Sign up to set email alerts
|

Is Fournier’s Gangrene Severity Index Useful for Predicting Outcome of Fournier’s Gangrene?

Abstract: Objectives: Fournier’s gangrene (FG) is a rare but life-threatening disease. Although antibiotics and aggressive debridement have been broadly accepted as the standard treatment, the mortality rate remains high. We conducted a retrospective study to analyze the outcome and identify the risk factors and prognostic indicators. Methods: We retrospectively reviewed the medical records of 25 patients diagnosed with FG between July 1993 and August 2003. Data collected included age, predisposing factors, treatment mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
24
0
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 20 publications
2
24
0
4
Order By: Relevance
“…Unlike our study, Tuncel et al [2] found significant differences between survivors and nonsurvivors in albumin and ALP levels. Similarly, Lin et al [20] found that serum albumin levels between survivors and nonsurvivors at admission were significantly different.…”
Section: Discussionmentioning
confidence: 94%
“…Unlike our study, Tuncel et al [2] found significant differences between survivors and nonsurvivors in albumin and ALP levels. Similarly, Lin et al [20] found that serum albumin levels between survivors and nonsurvivors at admission were significantly different.…”
Section: Discussionmentioning
confidence: 94%
“…Lin E, and others suggested that a FGSI cutoff of 9 was an excellent predictor of outcome of cases. 24 However, diagnosis, treatment and the arrest of the gangrene at an early stage markedly improve outcome. A study conducted by Tuncel et al on 20 Fournier's gangrene patients concluded that FGSI did not predict the disease severity and the patient survival.…”
Section: Discussionmentioning
confidence: 99%
“…This index was based on data gathered from only 30 patients presenting to a referral center over a 15-year period. Other investigators reported variable accuracy using the Fournier's Gangrene Severity Index to predict mortality [13,14,15,16,17,18]. …”
Section: Introductionmentioning
confidence: 99%